A novel Pt(iv) mono azido mono triazolato complex evolves azidyl radicals following irradiation with visible light. Issue 19 (23rd April 2019) - Yao, Kezi; Bertran, Arnau; Morgan, Jacques; Hare, Samuel M.; Rees, Nicholas H.; Kenwright, Alan M.; Edkins, Katharina; Bowen, Alice M.; Farrer, Nicola J.
Abstract : A novel Pt IV azido triazolato complex exists as an equilibrium between two species in d 3 -MeCN and evolves azide radicals (but not hydroxide radicals) when irradiated with visible light. Abstract : The platinum(iv ) azido complex trans, trans, trans -[Pt IV (N3 )2 (OH)2 (py)2 ] (1 ) undergoes cycloaddition with 1, 4-diphenyl-2-butyne-1, 4-dione (2 ) under mild, catalyst-free conditions, affording a number of mono and bis click products. The major mono click product (3 ) exists in MeCN as an equilibrium mixture between two species;3a and3b rapidly interconvert through nucleophilic attack of the axial Pt–OH group at the adjacent Ph–CO group. The kinetic and thermodynamic parameters for this interconversion have been measured by selective saturation-transfer NMR spectroscopic experiments and are consistent with cyclisation at the Pt centre. Complex3b was also characterised by X-ray crystallography. Visible light irradiation (440–480 nm) of3 in d 3 -MeCN produces azidyl radicals (N3 ˙), as demonstrated by EPR spin-trapping with DMPO; no generation of hydroxyl radicals was observed. 1 H– 195 Pt HMBC NMR confirmed that the photoproducts were Pt IV rather than Pt II species, and HPLC was consistent with these being [3 –N3 ] + species; no facile photoejection of the triazolato ligand was observed, consistent with MS/MS fragmentation of3 . When3 was irradiated in the presence of 5′-GMP, no 5′-GMP photoproducts were observed, suggesting that complex3 is likely to exhibit significantly simplified biological activity (release of azidyl radicals but not DNA binding) compared with complex1 .